The Doha Development Agenda : What's on the Table? - Martin, Will; Mattoo, Aaditya (World Bank, Washington, DC, 2012)
The outlines of a potential agreement, emerging after seven years of negotiations, imply that Doha offers three key benefits: reduced uncertainty of market access in goods and services; improved market access in agriculture and manufacturing; and the mobilization of resources to deal with the trade problems of least developed countries. WTO Members have offered to make large reductions in legally bound levels of protection in goods and services. The reductions in currently applied levels of protection are smaller. For the least developed countries, the proposed "duty free and quota free" access will only add significantly to their access under existing preferential access arrangements if industrial and developing country members include vital tariff lines. The initiatives on trade facilitation and aid for trade can play a valuable catalytic role in promoting reform and mobilizing assistance, but substantial effort is still needed to translate notional benefits into actual gain.